Hutang Optimal dan Nilai Perusahaan di Indonesia: Studi Pada Perusahaan yang Listing di BEI - Aulia Keiko Hubbansyah; Lailah Fujianti; Safitri Siswono (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2021)
This study aims to identify the optimal portion of debt in the capital structure that maximizes the firm value. Using the panel threshold estimation approach and company data listed on the Indonesia Stock Exchange for 2012-2019, this study provides strong empirical evidence that there is a non-linear relationship between debt and firm value. In this case, it is found that the optimal portion of debt for companies in Indonesia ranges from 48 - 54 percent relative to its equity. As shown this level of debt is empirically proven to have the greatest positive impact on increasing the firm value. But, when the portion of debt that exceeds 54 percent, it has no impact on the firm value. Meaning that the impact of additional debt on firm value will be insignificant, and only increase the level of the debt. Keywords: Firm value, firm debt, dividend, managerial ownership